Ethics, advertising and the definition of a profession. - Dyer, A R (1985)
In the climate of concern about high medical costs, the relationship between the trade and professional aspects of medical practice is receiving close scrutiny. In the United Kingdom there is talk of increasing privatisation of health services, and in the United States the Federal Trade Commission (FTC) has attempted to define medicine as a trade for the purposes of commercial regulation. The Supreme Court recently upheld the FTC charge that the American Medical Association (AMA) has been in restraint of trade because of ethical strictures against advertising. The concept of profession, as it has been analyzed in sociological, legal, philosophical, and historical perspectives, reveals the importance of an ethic of service as well as technical expertise as defining characteristics of professions. It is suggested that the medical profession should pay more attention to its service ideal at this time when doctors are widely perceived to be technically preoccupied.